AUTOIMMUNE BULLOUS DERMATOSES. DIFFERENTIAL DIAGNOSIS - V. I. Al'banova; M. A. Nefedova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The review presents modern ideas concerning autoimmune bullous dermatoses (pemphigoid group): Duhring disease, bullous pemphigoid, cicatrizing pemphigus, pemphigoid gestationis, linear IgA bullous dermatosis and acquired bullous epidermolysis. Pathogenesis, clinical manifestations and modern methods of disease diagnostics are reported. Particular attention is paid to the diagnosis of acquired bullous epidermolysis, in which the leading role belongs to the reaction of immunofluorescence. The pathogenetic similarity between bullous pemphigoid, linear IgA dermatosis, cicatrizing pemphigoid and pemphigoid gestationis is shown, which allows us to regard them as a variety of a single pathological process.